A clinical nutritional information system with personalized nutrition assessment. (March 2018) - Kuo, Su-E; Lai, Hui-San; Hsu, Jen-Ming; Yu, Yao-Chang; Zheng, Dong-Zhe; Hou, Ting-Wei
Highlights: The Clinical Nutritional Information System (CNIS) was constituted design and implementation based on the Nutrition Care Process and Model (NCPM) and Patient Nutrition Care Process. Dietitians used CNIS, 95% reported satisfaction with 91.66% indicating that CNIS is really helpful in their work. Approximately 58% work time was saved with the assistance of CNIS. Abstract: Background and objective: Traditional nutrition evaluations not only require the use of numerous tables and lists to provide sufficient recommendations for patients' diets but are also very time-consuming due to cross-referencing and calculations. Methods: To personalize patient assessments, this study implemented a Clinical Nutritional Information System (CNIS) to help hospital dietitians perform their daily work more effectively in terms of time management and paper work. The CNIS mainly targets in-patients who require cancer-nutrition counselling. The development of the CNIS occurred in three phases. Phase 1 included system design and implementation based on the Nutrition Care Process and Model (NCPM) and the Patient Nutrition Care Process. Phase 2 involved a survey to characterize the efficiency, quality and accuracy of the CNIS. In Phase 3, a second survey was conducted to determine how well dietitians had adapted to the system and the extent of improvement in efficiency after the CNIS had been available online for three years. Results: The work time requirements decreased by approximately 58% with the assistance of the CNIS. Of the dietitians who used the CNIS, 95% reported satisfaction, with 91.66% indicating that the CNIS was really helpful in their work. However, some shortcomings were also evident according to the results. Conclusions: Dietitians favoured the standardization of nutritional intervention and monitoring. The CNIS meets the needs of dietitians by increasing the quality of nutritional interventions by providing accurate calculations and cross-referencing for information regarding patients' conditions, with the benefit of decreasing the processing time, such as handwritten documentation. In addition, the CNIS also helps dietitians statistically analyse each patient's personal nutritional needs to achieve nutritional improvement.